Bioremediation pretreatment of waste-activated sludge using microalgae Spirulina platensis derived biochar coupled with sodium sulfite: Performance and microbial community dynamics. (October 2022) - Hung, Chang-Mao; Chen, Chiu-Wen; Huang, Chin-Pao; Dong, Cheng-Di
Graphical abstract: Highlights: A carbon-neutral and sustainable blue-green algae biochar (BGBC) was prepared. BGBC activated sodium sulfite (SS) with significant 4-NP removal from sludge matrices. The contributions of oxidizing species and functional groups to SS activation were evaluated. SS increased Denitratisoma abundance, a key microbe that degrades 4-NP in WAS. Abstract: 4-Nonylphenol is a typical endocrine-disrupting compound found in waste-activated sludge. This study evaluates the feasibility of blue-green algae ( Spirulina platensis )-based biochar as a carbon-neutral material to improve sodium sulfite (S(IV))-mediated sludge purification. Blue-green algae-based biochar is an effective activator (at 500 °C and 3 × 10 −6 M) of sodium sulfite and removed 75 % of 4-nonylphenol at pH 6 using at 1.7 g/L of dosage. Possible synergistic relationships among the coexisting oxidizing species (SO3 −, SO4 −, HO, and 1 O2 ), obvious defect structure, and abundant carbonyl oxygen groups on the surface of the biochar together dived advanced oxidation process. The bacterial consortia promoted the decomposition of biologically available substrates in the biosolid mixture, which led to the enrichment of Denitratisoma, and boosted 4-nonylphenol biodegradation. This study outlines a potential carbon–neutral, cost-effective, and sustainable sludge treatment strategy using renewable blue-green algae-based biochar, aiding 4-nonylphenol biodegradation in waste-activated sludge.